Gender Roles in the Value Chain of Farmed Tilapia (Oreochromis niloticus) in Kakamega County, Kenya - Nabayunga, S.; Matolla, G.; Shitotte, Z.; Kawooya Kubiriza, G.; Kondowe, B. N. (Africa Environmental Review Journal, 2021)
Aquaculture value chains provide a significant level of income and employment globally directly and indirectly. However, availability of gender disaggregated data on the contribution of the sector to the livelihoods is limited. This has resulted in women’s contribution in aquaculture being perceived as supportive and not equal player despite the many strides women are making in the sector. Therefore, the present study was conducted to evaluate the gender roles along the farmed tilapia value-chain in Kakamega County, Kenya. Respondents totaling 265 comprised of 200 fish farmers, 5 input suppliers, 30 traders and 30 consumers were sampled and interviewed using questionnaire. Descriptive statistics and Chi-square were used to analyze the data. Results revealed that producers/fish farmer’s segment was dominated by males (74.24%) compared to female (25.76%). Input suppliers comprised of one female and four males. Majority of fish traders were female (66.7%) compared to male (33.3%). Lastly, consumers comprised of more males (56.7%) than females (43.3%). Gendered data showed that men were mainly undertaking laborious activities such as pond construction, pond preparation, pond management, fish harvesting and fish feeding while women were mainly involved in fish trade and marketing. The only female input suppliers was involved in fingerling production while the males were engaged in all activities from fingerling production, feed supply, to supply of equipment. The identified gender obstacles along the value chain included limited land access by women, labor intensiveness, lack of capital, long payback time, poor aquaculture perception by women and inadequate information on aquaculture. Chi square test revealed no significant association between gender and various socio-economic variables (participation in training activities, technical assistance and source of assistance) except for belonging to groups (p = 0.0477). The men’s dominance in fish production probably explains cultural favoritism that allows them to easily access and own land which boosts their capital. Conversely, women probably dominated traders’ segment due to intrinsic management skills as de facto home managers. Nevertheless, there is need to break gender barriers to ensure recognition of women contributions to aquaculture.